At the Front Line : Reflections on the Bank’s Work with China over Forty Years, 1980-2020 - World Bank (World Bank, Washington, DC, 2021)
This volume contains written contributions from some of the key actors involved on both the Chinese and the World Bank sides in the past four decades of partnership. It is clear that the World Bank from the very beginning provided honest and evidence-based advice to China, but China was always in the driver’s seat in structuring the relationship and in determining what to do (and what not to do). Periodically, the World Bank engaged in national policy debates, during the Bashan Boat Conference, at Dalian, then with the China 2020 and China 2030 reports, and the subsequent series of flagships produced jointly with the Development Research Center under the State Council. For much of the time, however, World Bank’s impact was at the local level through demonstration projects and reform pilots that China studied, adapted, and later scaled. Finally, an increasingly important theme of the partnership in the last decade concerns World Bank’s cooperation with China globally, through International Development Association (IDA), South-South learning, and ongoing discussions over good practices in international development finance. As China’s global economic and financial heft continues to grow, this theme is likely to become increasingly important and require further adaptation on both sides. The first part contains the contributions of World Bank Country Directors in chronological order by decade: Caio Koch-Weser, Edwin Lim for the 1980s; Javed Burki, Pieter Bottelier, and Nick Hope for the 1990s; Yukon Huang and David Dollar for the 2000s; and Klaus Rohland and Bert Hofman for the 2010s. The second part contains the contributions of the Chinese authors, which are organized by themes. The third essay speaks to the shift in World Bank’s program to support China’s climate action following the Paris Agreement, with lessons that are highly relevant for the future evolution of the partnership. The fourth contribution is from Yang Yingming, former Executive Director for China at the World Bank, and now back with the Ministry of Finance, and reflects on the interaction between World Bank’s knowledge and financial cooperation with China, drawing lessons for other countries and for the future of the partnership.